Principles of Endocrinology and Hormone Action (Endocrinology, 2018)
This volume provides comprehensive coverage of the current knowledge of the physiology of the endocrine system and hormone synthesis and release, transport, and action at the molecular and cellular levels. It presents essential as well as in-depth information of value to both medical students and specialists in Endocrinology, Gynecology, Pediatrics, and Internal Medicine. Although it is well established that the endocrine system regulates essential functions involved in growth, reproduction, and homeostasis, it is increasingly being recognized that this complex regulatory system comprises not only hormones secreted by the classic endocrine glands but also hormones and regulatory factors produced by many organs, and involves extensive crosstalk with the neural and immune system. At the same time, our knowledge of the molecular basis of hormone action has greatly improved. Understanding this complexity of endocrine physiology is crucial to prevent endocrine disorders, to improve the sensitivity of our diagnostic tools, and to provide the rationale for pharmacological, immunological, or genetic interventions. It is such understanding that this book is designed to foster.